GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 8 species occurrences available in GBIF matching the query: DatasetKey: (Table 1) Proportion of Toxoplasma gondii seropositive arctic foxes (Alopex lagopus) by age group and geographic area. The dataset includes 8 records from 1 constituent datasets: 8 records from (Table 1) Proportion of Toxoplasma gondii seropositive arctic foxes (Alopex lagopus) by age group and geographic area.
Keywords: GBIF; biodiversity; species occurrences